Evaluation of land suitability for urban land‐use planning: Case study Dhaka city - Ullah, Kazi Masel; Mansourian, Ali (Wiley Online Library, 2022)
This article was published in The Transactions in GIS [©2015 Published by John Wiley & Sons Ltd] and the definite version is available at: https://doi.org/10.1111/tgis.12137 The Article's website is at: https://onlinelibrary.wiley.com/doi/10.1111/tgis.12137